Interview with Assoc. Prof. Dr. Rosita (Deputy Director of Research and Industrial Networking) - Maniam, Yuthandy (Universiti Teknologi MARA, Sarawak, 2009)
The interview highlights Assoc. Prof. Dr. Rosita's views and plans upon her appointment as the Deputy Director of Research and Industrial Networking at UiTM Sarawak. She reflects on the responsibilities of the new role, especially in strengthening research culture and enhancing industry-linked projects. Dr. Rosita aims to increase the commercialization potential of research, create a positive working environment, and inspire staff to be more involved in research activities. She emphasizes effective time management and expresses her commitment to contributing to the university's growth and societal impact through research.